KONSEP PEMBINAAN SPIRITUAL MENUJU MAQAM IHSAN DALAM PERSPEKTIF AL-GHAZALI DAN SAID HAWWA - Asmaji; Hamdani (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study examines the concept of spiritual development toward the maqām of Ihsan through the perspectives of two prominent Muslim scholars, Imam al-Ghazali and Said Hawwa. Using a library research method with a descriptive-comparative approach, this study analyzes key ideas related to tazkiyatun nafs, the purification of the soul, and their relevance to contemporary Islamic education. Al-Ghazali emphasizes the stages of takhalli, tahalli, and tajalli as an introspective spiritual framework centered on purifying the heart and controlling desires. In contrast, Said Hawwa presents a more contextually modern framework of tarbiyah ruhiyah, highlighting the integration of personal spiritual growth with social righteousness through collective religious engagement. The findings reveal that the perspectives of the two scholars complement each other: al-Ghazali provides a foundational model for individual spiritual refinement, while Said Hawwa expands the concept toward social involvement grounded in sincerity and ihsan. The synthesis of these two approaches offers substantial relevance for Islamic educational curricula, particularly in pesantren, by shaping students who are ethically grounded, spiritually conscious, and capable of embodying Ihsan in both personal and social life.